Hubungan Kualitas Kehidupan Kerja Perawat dengan Komitmen Organisasi di RSUD Ajibarang - Fitriana Ika dewi; Tri Sumarni; Arlyana Hikmanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Ntroduction: Nurses' organizational commitment is their wholehearted dedication to the mission, vision, and values of their employer or health care facility. The degree to which nurses value their work environment is a measure of their quality of work life. The methodology of this study was a cross-sectional research design based on total sampling and descriptive correlational analysis. Result: The results of analysis using software show that there is a significant relationship between the quality of nurses' work life and organizational commitment. Conclusion: Nurses' work life quality and organizational commitment are significantly related, with a p value of 0.001 (where p value <α = 0.05) and a correlation coefficient of 0.342, indicating a relationship between the two. The strength of the relationship between work life and organizational commitment is lower, tending towards a positive or equal relationship.